2005
DOI: 10.1111/j.1945-5100.2005.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Spallation recoil II: Xenon evidence for young SiC grains

Abstract: We have determined the recoil range of spallation xenon produced by irradiation of Ba glass targets with approximatly 1190 and approximatly 268 MeV protons, using a catcher technique, where spallation products are measured in target and catcher foils. The inferred range for (sup 126)Xe produced in silicon carbide is approximatly 0.19 µm, which implies retention of approximatly 70% for (sup 126)Xe produced in "typical" presolar silicon carbide grains of 1 µm size. Recoil loss of spallation xenon poses a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 67 publications
3
44
0
Order By: Relevance
“…As can be seen, the ages cover a large range. Most are larger than the limit set by 126 Xe (Ott et al 2005) and the highest values overlap with estimates for grain lifetimes in the ISM (Jones et al 1997). …”
Section: Lithium Isotopes and Cosmic-ray Exposure Agesmentioning
confidence: 76%
“…As can be seen, the ages cover a large range. Most are larger than the limit set by 126 Xe (Ott et al 2005) and the highest values overlap with estimates for grain lifetimes in the ISM (Jones et al 1997). …”
Section: Lithium Isotopes and Cosmic-ray Exposure Agesmentioning
confidence: 76%
“…Only one of the mainstream SiC grains analysed here falls into that age range. A possible explanation for young ages based on a Galactic merger 1.5-2 Gyr before Solar System formation (Clayton 2003) is discussed in Heck et al (2009) and Ott et al (2005). Interestingly, the two grains with the longest 21 Ne exposure are of type AB or possibly type AB (grains L2-57 and L2-25, respectively).…”
Section: Helium and Neon Agesmentioning
confidence: 99%
“…Conventional radiometric dating is hindered by small grain size, as well as the anomalous isotopic composition of essentially every element (Meyer & Zinner 2006). An alternative approach is to determine the length of time the grains were exposed to Galactic cosmic rays (GCR), by measuring GCR-produced nuclides, in particular, rare noble gas isotopes (Tang & Anders 1988b;Ott & Begemann 2000;Ott et al 2005). Studies made on aggregates of ∼micron-sized presolar SiC grains ('bulk samples') found GCR exposure ages of roughly 10 8 yr or less, considerably shorter than estimated lifetimes of interstellar dust (∼5 × 10 8 yr; Jones et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There are no equivalent data for 3 He in the literature that can be directly applied, and it is not possible to extrapolate from neon to helium as Ott and Begemann (2000) did to estimate the spallation xenon range (see also Ott et al 2005). This is because the dominant nuclear processes that lead to spallation 21 Ne (a large fragment) and spallation 3 He (a light fragment) are different.…”
Section: Appendixmentioning
confidence: 99%